Lenalidomide or bortezomib as maintenance treatment remedy the inferior impact of high-risk cytogenetic abnormalities in non-transplant patients with newly diagnosed multiple myeloma: a real-world multi-centered study in China - Zhuang, Zhe; Tian, Ying; Shi, Lei; Zou, Dongmei; Feng, Ru; Tian, Wei-wei; Yu, Hong; Dong, Fei; Liao, Aijun; Ma, Yanping; Liu, Qinhua; Liu, Shuangjiao; et al. (Frontiers in Oncology, 2023)
Maintenance treatment is a pivotal part in the whole process management of multiple myeloma (MM), which further deepens response and improves survival. However, evidence of maintenance in non-transplant MM patients is inadequate in real-world practice. Here, we retrospectively analyzed the efficacy and survival of 375 non-transplant MM patients from 11 centers between 2010 and 2021 in north China. After a median of seven cycles of front-line regimens, there were 141, 79, and 155 patients receiving lenalidomide maintenance (L-MT), bortezomib maintenance (B-MT), or thalidomide maintenance (T-MT), respectively. Patients on L-MT and B-MT had significantly greater proportions of high-risk cytogenetic abnormalities (HRCAs) detected by fluorescence in situ hybridization (FISH), which was defined as 1q21 gain, 17p deletion, adverse immunoglobulin heavy chain (IgH) translocations. Although the progression-free survival (PFS) and overall survival (OS) were comparable among the three groups, L-MT and B-MT remedied the negative impact of HRCAs on survival (PFS of patients with HRCAs vs. patients without HRCAs: L-MT, 26.9 vs. 39.2 months, p=0.19; B-MT, 20.0 vs. 29.7 months, p=0.36; OS not reached in all groups). Patients with HRCAs in the T-MT group presented inferior clinical outcomes compared to standard-risk patients (PFS, 12.1 vs. 22.8 months, p=0.02, HR=1.8, 95% CI 1.0–3.4; OS, 54.9 months vs. NR, p<0.001, HR=3.2, 95% CI 1.5–7.0). Achieving complete response (CR) after induction therapy led to superior PFS compared to other degrees of response, regardless of maintenance medication. Furthermore, maintenance duration over 24 months correlated with favorable survival. Due to the large gap of transplant eligibility in China, optimizing maintenance therapy is important for non-transplant MM patients. In this real-world multi-centered study, our findings suggest that clinicians prefer to prescribe lenalidomide or bortezomib as maintenance therapy in high-risk settings, which are superior to thalidomide in non-transplant MM patients. Achievement of CR and maintenance duration over 2 years are positive factors that influence survival.